How do technological changes in formal education shape the social roles of teachers who are mothers?. (July 2021) - Weisberger, Moriya; Grinshtain, Yael; Blau, Ina
Abstract: The teaching profession has become more demanding as a result of technology integration in teaching-learning-assessment processes. These changes are particularly challenging for teachers-mothers. This study aimed at understanding how technological changes that are integrated in the teaching profession shape the social roles of teachers-mothers. Semi-structured interviews were conducted with a diverse sample of thirty teachers-mothers. The analysis revealed main themes related to pedagogical aspects of technology integration, online professional development, and work-related e-communication. In addition, the categories of blurred boundaries, multichannel communication, and less free time were related to teachers-mothers' social roles. Theoretical and practical implications are discussed. Highlights: The teaching profession has become more demanding as a result of the integration of technology in teaching. The technological changes are particularly challenging for teachers who are mothers. The changes are pedagogical technology integration, online professional development, and work-related e-communication. Blurred boundaries, multi-channel communication, and less free time were related to teacher-mothers' social roles. When implementing technological changes, both the teaching sphere and the motherhood sphere should be considered.